A Comparison of Local Endolymphatic Sac Decompression, Endolymphatic Mastoid Shunt, and Wide Endolymphatic Sac Decompression in the Treatment of Intractable Meniere's Disease: A Short-Term Follow-Up Investigation - Zheng, Guiliang; Liu, Yupeng; He, Jingchun; Li, Shuna; Zhang, Qing; Duan, Maoli; Yang, Jun; Jin, Yulian (Frontiers in Neurology, 2022)
Background: Meniere’s disease (MD) is a common inner ear disease, characterized by recurrent attacks of vertigo, low-frequency sensorineural hearing loss, tinnitus and aural fullness. Endolymphatic sac surgery is an effective treatment to control vertigo attacks but without causing hearing loss for intractable MD. However, the methods and effects of endolymphatic sac surgery are controversial for many years and the relationship between the vertigo control rates of different endolymphatic sac surgery methods is not well documented. Objectives: This study compared the vertigo control rate, hearing outcome and quality of life (QOL) among different endolymphatic sac surgery including local endolymphatic sac decompression (LESD), endolymphatic sac mastoid shunt (ESMS) and wide endolymphatic sac decompression (WESD). Materials and methods: We retrospectively analyzed the patients who underwent endolymphatic sac surgery from January 2008 to June 2019. The control rate of vertigo and QOL scores were compared after two years of follow-up. The QOL was scored with validation of the MD patient-oriented symptom-severity index (MDPOSI). The pure tone thresholds of all patients at pre- and post-operation were also compared. Results: 83 MD patients with complete follow-up data were included in the study, including 20 patients with LESD, 28 patients with ESMS, and 35 patients with WESD. Results showed a better vertigo control with WESD than the other groups (70% with LESD，71.4% with ESMS, and 88.6% with WESD). The QOL were improved after surgery in all groups in which the difference was statistically significant (QOL, Preoperative vs. Postoperative, 38.2 vs. 10.1 with LESD, 37.8 vs. 9.6 with ESMS, 37.6 vs. 8.3 with WESD), respectively. After endolymphatic sac surgery, hearing was well preserved in the three groups (PTA, dB, Preoperative vs. Postoperative, 41.0±19.3 vs. 40.8±17.9 with LESD, 39.7±16.4 vs. 40.8±18.2 with ESMS, 38.5±18.7 vs.36.6±19.5 with WESD). Conclusion: WESD has higher vertigo control rate, better improvement of QOL and relatively higher hearing stability or improvement rate after surgery in patients with MD compared with LESD and ESMS.